Surface topography modulates initial platelet adhesion to titanium substrata - Cecilia Yan Guo; Raymond Mo; Hugh Kim (Elsevier, 2024)
The clinical success of implanted biomaterials such as dental implants is largely determined by the molecular signaling that occurs at the tissue-implant interface. The modification of surface topography is a widely-employed strategy for optimizing tissue integration with dental implants. However, little is known regarding the direct, cellular-level effects of substratum topography on platelet signaling and adhesion, despite these cells being the first to encounter the implant surface during surgical placement. Here we compared platelet adhesion and secretion on four (4) different titanium surfaces, notably, the modifications applied to commercially available dental implants: smooth (S) titanium; acid-etched (AE), sandblasted (SB) and a combined acid-etching/sandblasting procedure (SLA). Platelets were isolated from human blood, washed, and seeded on to the 4 test surfaces; platelet adhesion was quantified by microscopy. In addition, the secretion of critical molecules stored in platelet granules (platelet factor 4, PF4; soluble P-selectin, sCD62P; transforming growth factor-beta1, TGF-β1; platelet-derived growth factor-AB, PDGF-AB) was measured by enzyme-linked immunosorbent assay (ELISA) analysis of the supernatants. There was greater platelet adhesion to the rougher AE and SB surfaces, however, the concentration of the secreted growth factors was comparable on all surfaces. We conclude that while surface topography can be engineered to modulate initial platelet adhesion, granule secretion is likely regulated as a separate and independent process.